The longitudinal course of pediatric acute respiratory distress syndrome and its time to resolution: A prospective observational study - Judith Ju Ming Wong; Judith Ju Ming Wong; Herng Lee Tan; Rehena Sultana; Yi-Jyun Ma; Apollo Aguilan; Siew Wah Lee; Pavanish Kumar; Yee Hui Mok; Yee Hui Mok; Jan Hau Lee; Jan Hau Lee (Frontiers Media S.A., 2022)
BackgroundThe longitudinal course of patients with pediatric acute respiratory distress syndrome (PARDS) is not well described. In this study, we describe the oxygenation index (OI) and oxygen saturation index (OSI) in mild, moderate, and severe PARDS over 28 days and provide pilot data for the time to resolution of PARDS (Tres), as a short-term respiratory-specific outcome, hypothesizing that it is associated with the severity of PARDS and clinical outcomes.MethodsThis prospective observational study recruited consecutive patients with PARDS. OI and OSI were trended daily over 28 days. Tres (defined as OI < 4 or OSI < 5.3 on 2 consecutive days) were described based on PARDS severity and analyzed with Poisson and logistic regression to determine its association with conventional outcomes [mechanical ventilation (MV) duration, intensive care unit (ICU) and hospital length of stay, 28-day ventilator-free days (VFD), and 28-day ICU-free days (IFD)].ResultsThere were 121 children included in this study, 33/121(27.3%), 44/121(36.4%), and 44/121(36.4%) in the mild, moderate, and severe groups of PARDS, respectively. OI and OSI clearly differentiated mild, moderate, and severe groups in the first 7days of PARDS; however, this differentiation was no longer present after 7days. Median Tres was 4 (interquartile range: 3, 6), 5 (4, 7), and 7.5 (7, 11.5) days; p < 0.001 for the mild, moderate, and severe groups of PARDS, respectively. Tres was associated with increased MV duration, ICU and hospital length of stay, and decreased VFD and IFD.ConclusionThe oxygenation defect in PARDS took progressively longer to resolve across the mild, moderate, and severe groups. Tres is a potential short-term respiratory-specific outcome, which may be useful in addition to conventional clinical outcomes but needs further validation in external cohorts.